Life Cycle GHG Emission Comparison of Infant Nursing Using Breast Milk Versus Formula - Amonkar, Yash; Chowdhury, Nafisa; Song, Yiran; Wu, Jane Siyuan; Vaidya, Parth; Meinrenken, Christoph J. (Journal of Environmental Accounting and Management, 2026)
The choice between feeding an infant using breast milk or formula milk continues to be a topic of debate among nutritionists, health practitioners, and parents. This study compares the life cycle environmental impact of both infant feeding methods in terms of green-house gas (GHG) emissions. Prior environmental impact studies in this context have treated breast milk feeding as a zero GHG emission activity and thus concluded that formula milk feeding is an ‘environmentally harmful’ feeding method. While these views have reached wide audiences, they have not yet been subjected to more detailed scientific scrutiny. However, as this study highlights, there are a variety of GHG emissions associated with breast milk feeding, such as from additional caloric intake by the mother and the use of breast pumps, infant bottles, and milk refrigeration in-between feedings (lifestyle-dependent). The results of the analysis show that breast milk feeding contributes a total of 1,858 g CO2e/day compared to the 1,136 g CO2 e/day associated with formula milk feeding (base case). Further, for breast milk feeding, the mother’s additional caloric intake contributes about 66%, the end of life stage 13%, use phase 10%, packaging 8%, and outbound transportation 3% to the total GHG emissions. In the case of formula milk feeding, the raw materials contribute about 40%, inbound transportation 23%, use phase 13%, outbound transportation 12%, manufacturing 7%, and packaging 5% to the total GHG emissions. A sensitivity analysis was conducted to account for parameter uncertainty and shows that breast milk feeding (1,463-2,202 g CO2e/day) one infant, for typical mothers’ lifestyles, is indeed the larger contributor of GHG emissions as compared to formula milk feeding (873-1,400 g CO2e/day). Additional scenarios such as individual mothers’ lifestyle choices were analyzed and discussed as well. These show that, in some scenarios, breastfeeding mothers who are able to forego pumps and infant bottles altogether may incur less GHG emissions than mothers feeding formula milk.